Clinical Outcomes of Total or Partial Renal Artery Embolization in Patients with Spontaneous Renal Bleeding - Lee, Hyo Jeong; Oh, Chang Hoon; Cho, Soo Buem; Choi, Sang Lim (Current Medical Imaging, 2025)
AimsThe aim of this study was to evaluate renal artery embolization in patients with spontaneous renal artery bleeding based on detailed angiographic findings and a comprehensive analysis of its efficacy and clinical outcomes.Materials and MethodsThis retrospective study evaluated the outcomes of renal artery embolization in 18 cases among 15 patients (11 men and 4 women; mean age: 57.9 years) treated for spontaneous renal bleeding at our institution between March 2017 and October 2023. Data derived from abdominal computed tomography (CT) and arteriography were analyzed to assess the effectiveness of embolization.ResultsMost patients had end-stage renal disease or renal atrophy, with common findings on CT scans, including signs of active bleeding in 66.7% (10/15) and hematoma extending to the retroperitoneal space in 53.3% (8/15). Microcoils were commonly used for embolization (n = 10), with a technical success rate of 100% and primary and final clinical success rates of 80% and 100%, respectively. No major complications were reported during the follow-up, and clinical improvement was observed in all patients who underwent total embolization, with few instances of reduced hematoma size and renal atrophy.ConclusionTransarterial embolization is safe and effective for controlling spontaneous renal hemorrhage.
Keywords: Microcoil